Kesehatan Mental Pada Ibu Bekerja Di Indonesia: Scoping Review - Nurul Fajriyah Prahastuti (Universitas Muhammadiyah Gresik, 2026)
Background: Mental health in working mothers, which is often overlooked, can increase the risk of stress, anxiety, and burnout, thereby affecting life’s quality. Objective: This study aims to review the literature related to mental health issues among working mothers in Indonesia. Method: A scoping review method was employed following the PRISMA guidelines, with literature searches conducted in two main databases: Garuda and Google Scholar. The search used the keywords “mental health,” “working mothers,” and “Indonesia.” Inclusion criteria consisted of articles published between 2021 and 2025, written in Indonesian, and available in full text. Result: The selection process identified 11 complete articles that met the inclusion criteria for analysis. Overall, these studies found that resilience, emotion regulation, psychological well-being, social support, and several other factors are closely related to the mental health of working mothers in Indonesia. Conclusion: Working mothers’ mental health in Indonesia is shaped by both psychological and social determinants, highlighting the need for sustained support from family, workplace environments, and public policy initiatives.